Equilibrium unemployment and capital intensity under product and labor market imperfections - Heikki Kauppi; Erkki Koskela; Rune Stenbacka (Center for Economic Studies and ifo Institute (CESifo), 2004)
We study the implications of product and labor market imperfections for equilibrium unemployment under both exogenous and endogenous capital intensity. With endogenous capital intensity, stronger labor market imperfections always increase equilibrium unemployment. The relationship between the long-run unemployment and the intensity of product market competition is not necessarily monotonic, but there is an elasticity of substitution between capital and labor below one such that the long-run equilibrium unemployment is an increasing function of product market imperfections when the elasticity exceeds this threshold. Higher interest rates increase (decrease) the long-run equilibrium unemployment when the elasticity of substitution is below (above) one.
Keywords: E22; L11; J51; E24; 330; equilibrium unemployment; product market imperfections; capital intensity; wage bargaining; Arbeitslosigkeit; Arbeitsmarkttheorie; Unvollkommener Markt; Wettbewerb; Investition; Lohnverhandlungstheorie; Kapitalintensität; Theorie